HYPERGLYCEMIA STATUS AND ASSOCIATED FACTORS AMONG ADULTS AGED 18-69 YEARS IN HANOI, 2025 (Vietnam Journal of Community Medicine, 2026)
Objective: To assess the current status of hyperglycemia and some influencing factors in people aged 18-69 in Hanoi in 2025.Subjects and methods: A cross-sectional study was conducted among 2736 adults aged 18-69 years. Data were collected through structured questionnaires and blood glucose testing. Univariate and multivariate logistic regression analyses were performed to identify factors associated with diabetes mellitus.Results: The overall prevalence of diabetes mellitus was 11.84%, including 7.49% with a prior diagnosis and 4.35% newly detected through screening; the prevalence of prediabetes was 13.05%. The prevalence of diabetes increased with age and was higher in the 45-69 age group compared to the 18-44 age group (15.85% vs. 4.61%). Higher prevalence was also observed among males, individuals with lower educational attainment, and those residing in urban areas. Multivariate logistic regression analysis identified age 45-69 years (OR = 2.9; 95% CI: 2.0-4.1), a history of hypertension (OR = 2.5; 95% CI: 1.9-3.2), and overweight/obesity (OR = 1.3; 95% CI: 1.01-1.8) as independent factors associated with diabetes. Other factors, including sex, residence, knowledge, diet, smoking, alcohol consumption, and physical activity, were not statistically significant after adjustment (p > 0.05).Conclusion: The prevalence of diabetes and prediabetes in the community is considerable. Older age, hypertension, and overweight/obesity are key risk factors. Targeted prevention and management strategies focusing on high-risk groups are essential to reduce the burden of diabetes.
Keywords: Diabetes mellitus, prediabetes, risk factors, Hanoi.